Analysis of the Effect of Translation Techniques on the Quality of Assertive Speech Translation using Impoliteness Theory in “The Silkworm” and “The Cuckoo's Calling” Novels - Waluyo, Yoyok Sabar; Iswara, Ratna Widya (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
The study of translation has been widely discussed and used as a research topic in the last decade, and this research contributes to that body of work. The focus of this study is on two detective novels,